(untitled) (Comprehensive Journal of Science, 2026)
This study investigates the proficiency of university English Language students in translating scientific texts in their contexts. The main aim of the study is to identify the translation techniques used by the students in translating scientific texts from English into Arabic. For this purpose, the researcher asked 20 students from the English Department, Faculty of Art, Zawyia University, to translate scientific texts using appropriate translation techniques. The students’ translations were analyzed in view of common translation techniques identified by translation scholars such as Newmark, Byrne, Molina and Hurtado Albir and Munday. The study findings show that the students lack the necessary knowledge and skills needed for translating scientific texts from English into Arabic, especially the use of translation techniques such as modulation, transposition, omission, restructuring and addition.